Cost savings and safety of ICD remote control by telephone: a prospective, observational study - Bikou, Olympia; Licka, Manuela; Kathöfer, Sven; Katus, Hugo; Bauer, Alexander (Journal of telemedicine and telecare, 2010)
We examined the costs and safety of follow-up of patients with an implantable cardioverter defibrillator (ICD). In a prospective study, a remote monitoring system was used to interrogate ICD devices via telephone. Twenty patients with an ICD were followed up conventionally (clinic visits) or remotely at 1, 3 and 6 months after implantation of the ICD. A total of 30 transmissions of ICD data were made via the remote monitoring system. Five transmissions (17%) were interrupted, mainly due to a loss of telemetry, but no data were lost. The duration of the remote follow-up was 12.7 min less than follow-up in clinic (25.8 min, P < 0.05). Five of the remote follow-up transmissions concerned arrhythmia episodes. These lasted significantly longer than those without arrhythmia (16.6 vs. 4.9 min, P < 0.05). In three patients an unscheduled visit to the outpatient clinic was necessary. The cost of remote follow-up for 100 ICD patients/year was calculated to be €44,267, or about 16% of the cost of conventional in-clinic follow-up.
Online veröffentlicht: 24. September 2010
Gesehen am 01.02.2023